(untitled) (Sains Humanika, 2015)
Social media is a new tool for an easy, fast and effective medium in distributing and obtaining information. Social media such as Facebook, YouTube, Instagram and Twitter are used by many teenagers these days, and most of them have social media accounts. YouTube is one of the media distribution agents that disseminate information, entertainment and news in the form of videos. The diverse functions of YouTube caused bully cases to be easily spread through the sharing of bullying-related videos; and such videos are commonly uploaded by the teenagers who involve in bully cases. The objective of this study is to investigate the response of social media users, via YouTube, towards bully cases among the teenagers in Malaysia. Four videos that show teens being bullied were purposively chosen as study cases. The contents of the video were transcribed and the responses or comments of viewers were analyzed and categorized. The findings show that majority of viewers were saddened and expressed their anger towards such video show. However a few viewers praised such behavior. With the help of social media such as YouTube, crime among the teenagers such as bully becomes viral in social media websites and its dissemination is irrespective of time and distance. This study contributes to the knowledge on the role of social media as distributing agent of information including crimes among teenagers, which need to be monitored and stopped, due to fear that bullying becomes a common phenomenon especially among the youth. Â